Axial load behaviour of pierced profiled composite walls with strength enhancement devices. (July 2015) - Hossain, Khandaker M.A.; Mol, Lukas K.; Anwar, Muhammed S.
Abstract: This paper presents the results of experimental and theoretical investigations on a novel form of pierced double skin composite wall (DSCW) system consisting of two skins of profiled steel sheeting with an in-fill of concrete. Nineteen composite walls are tested to failure under axial loading. The test variables include: types of profiled steel sheeting, types of load transfer device, size/orientation of opening/holes, wall height and types of strength enhancement devices around holes. The effects of each of these variables on axial load–deformation response, axial strength, steel–sheet concrete interaction, failure modes (including concrete core cracking and steel sheet buckling) and stress–strain development are critically evaluated. Strengthening of hole boundaries is found to be essential in enhancing the axial strength of the walls. The performance of strength enhancement devices installed in the walls is found satisfactory based on axial strength–deformation characteristics and failure modes of walls. Theoretical model for the prediction of axial strength of both pierced and non-pierced composite walls is developed taking into consideration the reduction of concrete capacity due to profiling and buckling of steel sheeting. The performance of the model is validated through comparisons with experimental results. Highlights: Investigation on a novel form of double skin perforated profiled composite wall Effect strength enhancement devices and geometry of perforations on load resistance Performance evaluation based on strength, deformation, stress–strain & failure mode Develop theoretical models for axial strength and performance validation